Achieving Stable Molybdenum Oxide Cathodes for Aqueous Zinc‐Ion Batteries in Water‐in‐Salt Electrolyte. Issue 9 (3rd February 2021) - Wang, Lei; Yan, Shan; Quilty, Calvin D.; Kuang, Jason; Dunkin, Mikaela R.; Ehrlich, Steven N.; Ma, Lu; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.
Abstract: Layered MoO3 represents a promising cathode for aqueous rechargeable Zn‐ion batteries, but the implementation of this material is limited due to the low conductivity and poor structural stability. A 30 m ZnCl2 water‐in‐salt electrolyte (WISE) is introduced to a MoO3 nanobelt cathode for the first time, significantly increasing the stability of MoO3 cathodes compared to those in 3 m ZnSO4 and 3 m ZnCl2 . The Zn/MoO3 cell in WISE unambiguously demonstrate significantly improved rate performance delivering 349, 253, and 222 mAh g −1 at 100, 500, and 1000 mA g −1, denoting a 12× capacity increase of those achieved in 3 m electrolytes at 1000 mA g −1 . A capacity retention rate of 73% is achieved after (dis)charging at 100 mA g −1 for 100 cycles, and no obvious capacity fading is observed at higher current densities of 500 mA g −1 and 2 A g −1 . Specifically, the data suggest that the drastic fading in 3 m electrolytes can be attributed to the parasitic surface deposits on Zn originated from Mo dissolution and H2 formation due to Zn corrosion and hydrogen evolution reaction, which are significantly suppressed in the WISE. The direct visualization of these side reactions is achieved for the first time in the Zn‐MoO3 system, using an in situ optoelectrochemical measurement. Abstract : A 30 m ZnCl2 water‐in‐salt electrolyte (WISE) is introduced to a MoO3 cathode for the first time in rechargeable zinc ion batteries, significantly increasing the cycling stability compared to that of 3 m ZnSO4 and 3 m ZnCl2 . In situ and ex situ structural, morphological, optical, and electrochemical characterizations are utilized to systematically investigate the improved stability in WISE.